2023
DOI: 10.1021/acs.jpclett.3c01889
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-Breaking Charge Separation in a Chiral Bis(perylenediimide) Probed at Ensemble and Single-Molecule Levels

Philip Daniel Maret,
Devika Sasikumar,
Ebin Sebastian
et al.

Abstract: Chiral molecular assemblies exhibiting symmetry-breaking charge separation (SB-CS) are potential candidates for the development of chiral organic semiconductors. Herein, we explore the excited-state dynamics of a helically chiral perylenediimide bichromophore (Cy-PDI 2 ) exhibiting SB-CS at the ensemble and single-molecule levels. Solvent polarity-tunable interchromophoric excitonic coupling in chiral Cy-PDI 2 facilitates the interplay of SB-CS and excimer formation in the ensemble domain. Analogous to the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 80 publications
(143 reference statements)
0
13
0
Order By: Relevance
“…The ESA at ∼682 nm represents the characteristic spectral signature of the singlet excited-state ( 1 PDI-T* ) of the parent ref-PDI monomer. ,, Within 36.8 ps, the 1 PDI-T* state decays with the evolution of a new transient species exhibiting a broad ESA at ∼548 to 750 nm. The newly formed transient species shows two peak maxima at ∼577 and 680 nm, relatively similar to the transient spectral feature of ref-PDI’s radical cation ( PDI •+ ) and radical anion ( PDI •– ), respectively. ,,, However, the ESA feature is broader than the typically observed spectroscopic signatures of CSS in PDI chromophores . The broadening of the spectral trace could be due to the incomplete CS in PDI-T in TOL, which is assigned to a CT state. ,, At higher time delays, The CT state decays to give rise to a new species having positive ESA with a maximum at ∼550 nm.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…The ESA at ∼682 nm represents the characteristic spectral signature of the singlet excited-state ( 1 PDI-T* ) of the parent ref-PDI monomer. ,, Within 36.8 ps, the 1 PDI-T* state decays with the evolution of a new transient species exhibiting a broad ESA at ∼548 to 750 nm. The newly formed transient species shows two peak maxima at ∼577 and 680 nm, relatively similar to the transient spectral feature of ref-PDI’s radical cation ( PDI •+ ) and radical anion ( PDI •– ), respectively. ,,, However, the ESA feature is broader than the typically observed spectroscopic signatures of CSS in PDI chromophores . The broadening of the spectral trace could be due to the incomplete CS in PDI-T in TOL, which is assigned to a CT state. ,, At higher time delays, The CT state decays to give rise to a new species having positive ESA with a maximum at ∼550 nm.…”
mentioning
confidence: 79%
“…The Ag/Ag + and glassy carbon electrodes were used as the reference and working electrodes, respectively. 19 56 The fluorescence-lifetime imaging microscopy (FLIM) images were acquired for PDI-T in PS and PVA (Figure 3a and 3b). The fluorescence intensity trajectories (FITs) of the PDI-T molecule were recorded by exciting the sample at 510 nm with a repetition rate of 20 MHz (Figures S19 and S20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Depending not only on the nature of the monomers but also on their mutual orientation and distance, multichromophoric arrays can undergo vastly different excited-state dynamics such as excimer formation, , enhanced intersystem crossing via singlet fission, , excitation energy hopping, ,, or symmetry-breaking charge separation (SB-CS). , This latter phenomenon is particularly attractive as it allows for the optical generation of a charge-separated state with minimal thermal losses, using a single dye that acts not only as an absorber but also as an electron donor and acceptor. Until now, SB-CS was reported with a limited number of dyes, including perylene, , perylene mono- and diimides, naphthalene diimides, , and anthracene and dipyrrin derivatives. These studies revealed that the occurrence of this process depends not only on the redox properties of the dyes, hence on the driving force, but also on the electronic coupling. Short interchromophoric distances enabling large coupling were found to be detrimental for SB-CS because they generally result in the formation of excimers, which act as traps. ,,, …”
mentioning
confidence: 99%